Deposition of a Silicon Carbide Reinforced Metal Matrix Composite (P25) Layer Using CO2Laser - Yip, M.W.; Barnes, S.; Sarhan, A.A.D. (American Society of Mechanical Engineers (ASME), 2015)
The objective of this research was to deposit a silicon carbide (SiC) reinforced layer of P25 (iron-based matrix material) on substrate material surface using CO2 laser. Two experiments using CO2 laser were carried out in this research. In the first experiment set, a gravity feed system was used with one powder feed containing different percentages of SiC particles and iron-based powder. In the second experiment set, preplaced powder was placed on substrate material surface. According to the experimental results, only few SiC particles were found in the clad matrix in the first experiment, and no SiC particles were found in the second experiment. A high microhardness value was noted in the SiC clad (above 1000 HV) in the first experiment compared to the second experiment with hardness values ranging from 200 HV to 700 HV. This was due to the high precipitation of carbide particles in the clad material during the first experiment. A comparison of the two different experiments signifies that the first one was the best because a more uniform layer with less porosity was produced.